Cardiac Toxicity in the Treatment of Light Chain Amyloidosis: Systematic Review of Clinical Studies - Jattin-Balcázar, Jairo J.; Quiroga-Ramírez, Paula Andrea (Current Drug Safety, 2024)
Background: Light chain amyloidosis (AL) is a progressive and a fatal disease that primarily affects cardiac tissue. Although the current approach to anti-amyloidosis treatments has managed to reduce amyloidosis morbimortality, the dynamics of cardiac adverse events are unknown. Objective: to provide evidence about reported cardiac toxicity during treatment of AL amyloidosis through a systematic review of the literature. Methods: A search was performed for registered clinical trials on ClinicalTrials.gov filtered for AL amyloidosis up to December 31, 2022. Studies were filtered by those that reported intervention in patients with AL amyloidosis and that had reported adverse events. The type of study, the intervention performed, and the frequency of reported cardiac adverse events were discriminated from each trial. Results: 25 clinical trials were analyzed, representing a population of 1,542 patients, among whom 576 (38.95%) adverse events were reported, 326 being serious (SAE) and 242 nonserious (nSAE). The most frequent SAEs were cardiac failure, atrial fibrillation, and cardiac arrest, while the most frequent nSAEs were palpitations, atrial fibrillation, and sinus tachycardia. Conclusion: cardiac toxicity during treatment for amyloidosis seems common, and it is important to evaluate the relationship of therapies with its occurrence.
Keywords: heart failure